Blind equalization - Luise, M.
A novel equalization/detection algorithm for orthogonal frequency division multiplexing (OFDM) signals transmitted over frequency-selective channels is introduced and investigated. The algorithm stems from the recognition that the Fourier transform processing inherent in OFDM turns a single wideband frequency-selective channel into a set of correlated narrowband frequency-flat fading channels. This suggests that sequence detection techniques, such as those discussed by Vitetta et al. (see IEEE Trans. Commun., vol.43, p.2750-8, 1995, IEEE Trans. Commun., vol.43, pt.II, p.1256-9, 1995, and Proc. IEEE Commun. Theory Mini-Conf (Globecom '96), London, UK, p.153-7, 1996), for time-selective flat-fading channels, can be also profitably utilized for joint equalization and decoding of OFDM signals in the frequency domain. Simulation results show that the proposed detection strategy, implemented via a standard Viterbi algorithm, provides improved performance over differential detection, with a moderate increase in receiver complexity and without requiring the periodic transmission of training blocks
Keywords: Fourier transform processing; OFDM signals; PSK signals; Viterbi algorithm; Blind detection; Blind equalization; Correlated narrowband frequency-flat fading channels; Decoding; Differential detection; Equalization/detection algorithm; Frequency domain; Joint equalization; Multipath fading; Orthogonal frequency division multiplexing; Receiver complexity; Sequence detection; Simulation results; Time-selective flat-fading channels; Wideband frequency-selective channel